IMPLEMENTASI TEKNIK SUPERVISI AKADEMIK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - ABBAS, ABBAS (DIDAKTIKA, 2018)
Supervision is a professional supervision, because it is also more specific in addition to observing academic activities that are based on scientific ability, and the approach is no longer the usual management supervision, but more demanding democratic and humanistic professional abilities by education supervisions. Supervision carried out by supervisors using group techniques, namely through activities such as: orientation meetings, teacher meetings, group studies between teachers, discussions as an exchange of thoughts or opinions, workshops, sharing of experiences, panel discussions, seminars and symposiums. In addition to group supervision techniques used also use individual techniques. Individual supervision techniques used by supervisors in carrying out teaching supervision programs such as class visits, classroom observations, intervisitation, self-assessment, teaching demonstrations, and supervision bulletins. Based on the implementation of various academic supervision techniques, the teacher is expected to have competence so that the learning process is conducive.